The Effects of Tail-Tilt on the Yaw Stability of Baseline-V Blended Wing Body Aircraft / Nur Syazwani C.M and Rizal E.M. Nasir - C.M., Nur Syazwani; M. Nasir, Rizal E. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper presents a study on the effects of tilting the tail on yaw stability performance of Baseline-V blended wing body (BWB) aircraft. The study on BWB aircraft began in UiTM in 2005 and a few designs of BWB aircraft have been studied and published. Recent progress on BWB study in UiTM indicates major flaws in BWB technology particularly its stability and issues regarding limited controllability since it is unequipped with any vertical tail to perform directional motion. Some ideas have been proposed generally to overcome the problems such as designing large central elevator on Baseline-I, attaching canard and belly-flap on Baseline-II, general shape mimics flying birds for Baseline-III and birds inspired control surface by adding horizontal tail for Baseline-IV. The results showed that some of the ideas gave positive feedback into stability and some degraded the aerodynamic efficiency. Even to this day, in general the research community and industry have not concluded any solutions or guidelines to overcome some problems of BWB aircraft design. It is proposed that the Baseline-V BWB aircraft to have a horizontal close-coupled tail located at wing trailing edge inspired by bird control surface so that longitudinal (pitch) and lateral-directional (yaw) stability suffered by BWB aircraft are solved. The objective of this study was to determine the effectiveness of close-coupled tail on Baseline-V BWB to overcome the problems regarding stability. This was achieved by conducting wind tunnel tests at low speed tunnels at Universiti Teknologi Malaysia (UTM-LST). The test model was a full scale model of Baseline-V and was tested at actual test speed of 15m/s (54 km/h). The longitudinal and lateral directional aerodynamic characteristics of the aircraft such as coefficients of forces (lift, drag and side forces) and coefficients of moments (roll, pitch and yaw moment) were experimentally measured. Based on the results, tilting tail of Baseline-V gave positive feedback in terms of stability. The Effects of Tail-Tilt on the Yaw Stability of Wing Body Aircraft